Heavy metals and yield of cowpea cultivated under composted tannery sludge amendment - Iuna Carmo Ribeiro Gonçalves; Ademir Sérgio Ferreira Araújo; Luis Alfredo Pinheiro Nunes; Antônio Aécio Carvalho Bezerra; Wanderley José de Melo (Acta Scientiarum. Agronomy, 2014)
The study aimed to evaluate the phytoavailability of heavy metals (Cr, Cd, Ni and Pb) concentrations in leaves and grains, and yield of cowpea (Vigna unguiculata L) grown in soil amended with composted tannery sludge (CTS) for two consecutive years. The experiments were carried out in 2009 and 2010 in soil amended with CTS at 0, 5, 10, 20, and 40 Mg ha-1. The CTS amendment rates applied were above 10 Mg ha-1, increased Cr concentrations in cowpea leaves. There were not increases in the heavy metals concentrations in cowpea grains after two years. In 2009, the application of CTS amendment did not promote increase in plant yield. However, in 2010, CTS amendment at 10 and 20 Mg ha-1 increased cowpea yield. The amendment of composted tannery sludge linearly increased linearly the concentration of Cr in the leaves of cowpea after two years. Composted tannery sludge promoted increases in cowpea yield.